2007
DOI: 10.1152/jn.00622.2006
|View full text |Cite
|
Sign up to set email alerts
|

Spastic Tail Muscles Recover From Myofiber Atrophy and Myosin Heavy Chain Transformations in Chronic Spinal Rats

Abstract: Harris RL, Putman CT, Rank M, Sanelli L, Bennett DJ. Spastic tail muscles recover from myofiber atrophy and myosin heavy chain transformations in chronic spinal rats. J Neurophysiol 97: 1040 -1051, 2007. First published November 22, 2006; doi:10.1152/jn.00622.2006. Without intervention after spinal cord injury (SCI), paralyzed skeletal muscles undergo myofiber atrophy and slow-to-fast myofiber type transformations. We hypothesized that chronic spasticity-associated neuromuscular activity after SCI would promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
48
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 49 publications
(90 reference statements)
2
48
0
1
Order By: Relevance
“…Spasticity is a velocity-dependent phenomenon characterized by increased muscle tone in response to passive movement. Spasticity has been previously shown to preserve slow-to-fast fiber conversion in the tail muscle of SCI rats [19]. As early as 6 weeks post-SCI, spasticity appears to exert a protective effect on skeletal muscle size and composition in those with a high level of injury compared with nonspastic individuals with a low level of injury [8].…”
Section: Discussionmentioning
confidence: 96%
“…Spasticity is a velocity-dependent phenomenon characterized by increased muscle tone in response to passive movement. Spasticity has been previously shown to preserve slow-to-fast fiber conversion in the tail muscle of SCI rats [19]. As early as 6 weeks post-SCI, spasticity appears to exert a protective effect on skeletal muscle size and composition in those with a high level of injury compared with nonspastic individuals with a low level of injury [8].…”
Section: Discussionmentioning
confidence: 96%
“…First, spastic muscles might attenuate the shift in slow-to-fast muscle fiber transformation; slow fibers have a higher mitochondrial concentration that may be responsible for the increased fat oxidation. 22,23 Second, SCI is characterized by diminished growth hormone (GH), insulin-like growth factor-1 (IGF-1) and testosterone; the decline in anabolic hormones may further exacerbate muscle atrophy and FM gain below the level of injury. [24][25][26] Spasticity may provoke muscular IGF-1 that compensates for the reduced growth hormone-IGF-1 axis after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mechanisms through which severe spasticity ameliorates the derangement of body compositions and glucose homeostasis could be investigated. For example, differences in the expression of glucose transport protein, GLUT4 proteins, 30 IGF-1 concentration 7,29 and muscle fiber type composition 22,23 have been suggested as related mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It is sometimes even quite the opposite. Indeed, we have recently shown that neuronal activity in the form of muscle spasms actually prevents muscle atrophy and changes in muscle properties (Harris et al 2006(Harris et al , 2007. So the nonspasming muscles atrophy and the spasming muscles do not atrophy, which raises the question of how vigorously we should treat spasticity with drugs like baclofen (Li et al 2004c).…”
mentioning
confidence: 99%
“…Dietz dismisses all the animal models, especially our sacral spinal rat, because he thinks that they do not have changes in muscle properties similar to those seen in his stroke patient groups (Dietz 2007;Dietz and Sinkjaer 2007). Ironically, however, it is our sacral spinal rat model that might be most useful to his investigations of muscle properties (Harris et al 2006(Harris et al , 2007 because we have shown that the muscle properties of sacral spinal rats do change very much as in humans after spinal cord injury (Thomas and Ross 1997;Zijdewind and Thomas 2003). Interesting, in muscles that exhibit lots of spasms, this motoneural activity tends to help preserve muscle properties, preventing atrophy, although not completely preventing increased contractures (Harris et al 2006(Harris et al , 2007.…”
mentioning
confidence: 99%